2016
DOI: 10.4271/2016-01-0497
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Impact Damage, Residual Strength and Crashworthiness of Composite Structures

Abstract: The development of the latest generation of wide-body carbon-fibre composite passenger aircraft has heralded a new era in the utilisation of these materials. The premise of superior specific strength and stiffness, corrosion and fatigue resistance, is tempered by high development costs, slow production rates and lengthy and expensive certification programmes. Substantial effort is currently being directed towards the development of new modelling and simulation tools, at all levels of the development cycle, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The resulting damaged samples are then clamped within a support fixture, and loaded in compression, to determine the residual strength. A consistent relation between impact energy and CAI strength of composite laminates has been shown in previous studies [11][12][13][14].…”
Section: *Manuscript Click Here To View Linked Referencessupporting
confidence: 88%
“…The resulting damaged samples are then clamped within a support fixture, and loaded in compression, to determine the residual strength. A consistent relation between impact energy and CAI strength of composite laminates has been shown in previous studies [11][12][13][14].…”
Section: *Manuscript Click Here To View Linked Referencessupporting
confidence: 88%
“…A number of papers by Falzon's research group [2,3,8,10] have reported excellent correlation between experimental impact tests and predictive computational modelling. Moreover, recent developments have further demonstrated the ability of this damage model to accurately predict compression-afterimpact behaviour [3] and assess the crushing response of composite specimens [4,9,11]. These studies attest to the robustness and stability of the damage model.…”
Section: Application On a Low Velocity Impact (Lvi) Modelmentioning
confidence: 99%
“…Thermoplastic composites, compared with thermoset ones, show a significant higher production speed and better repairability and recyclability. These characteristics make thermoplastic composites valuable alternatives to thermoset composites and metals in many sectors, especially in automotive industry [1]. Acrylic resins are lightweight thermosetting plastics with excellent wetting properties and a high strength, making them useful for ultralight orthopaedic appliances too.…”
Section: Introductionmentioning
confidence: 99%